The price of liquidity: Bank characteristics and market conditions - Falko Fecht; Kjell G. Nyborg; Jörg Rocholl (Universität Zürich, Institut für schweizerisches Bankwesen, 2010)
We identify frictions in the market for liquidity as well as bank-specific and market-wide factors that affect the prices that banks pay for liquidity, captured here by borrowing rates in repos with the central bank and benchmarked by the overnight index swap. We have price data at the individual bank level and, unique to this paper, data on individual banks' reserve requirements and actual reserve holdings, thus allowing us to gauge the extent to which a bank is short or long liquidity. We find that the price a bank pays for liquidity depends on the liquidity positions of other banks, as well as its own. There is evidence that liquidity squeezes occasionally occur and short banks pay more the larger is the potential for a squeeze. The price paid for liquidity is decreasing in bank size and small banks are more adversely affected by an increased potential for a squeeze. Healthier banks pay less, but contrary to what one might expect, banks in formal liquidity networks do not.
Keywords: G12; G21; E43; E58; D44; 330; banks; liquidity; money markets; repos; short squeezing; financial health; Bankenliquidität; Geldmarkt; Repo-Geschäft; Zins; Finanzsystem; Deutschland